Child-centred Design Decisions – How Children’s Participation in the Design Process Influences Design Students’ Decisions when Designing for Play - Feder, Karen (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This qualitative design research study looks at how children’s participation in the design process influences design students and their decisions when designing for play. The study analyses the experiences and reflections of 16 design students collaborating online with children around the world and identifies challenges and opportunities regarding this way of working. One case example illustrates how a design student (Paula) is able to acquire a better understanding of a child (Pedro) and his everyday life and uncover cultural challenges for the child’s opportunity to play. The article concludes on how a more balanced design process that includes collaboration with children can make design students become more aware of the cultural context they are designing for, leading to the potential of more child relevant play experiences.